Developing creativity: a new paradigm - Nizhneva-Ksenofontava, Nadzeya; Nizhneva, Natallia (Scripta Neophilologica Posnaniensia, 2019)
The article is devoted to the description of a new teaching paradigm, a paradigm of developing creativity in particular. Difference between a new paradigm and the old one is shown. The essence of such concepts as thinking, critical thinking, creative thinking, creativity is analyzed. Peculiarities of thinking of geniuses are described. The author presents critical thinking skills. Special attention is paid to barriers to creativity, essence of creative situations, their most distinctive features, main parameters, key principles of developing creative situations.